Adolescents' reasons for making facebook content visible or not visible from their mothers - Del Mundo, Jovie Angelie C.; Foronda, Jennifer Camille N.; Reyes, Dannah S. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT Social Networking Sites, especially Facebook has created a change in the way Internet users connect online (Dor & Weimann-Saks, 2012). It is also an avenue to improve and enhance relationship of an adolescent to his/her parents (Kanter, Afifi and Robbins, 2012). Since Facebook has created a change in the way Internet users connect online, this study focuses on reasons why adolescents share or hide Facebook Content when they are Facebook friends with their mother. The purpose of this study is to explore the adolescents' Facebook Content that they reveal or hide and why they chose such settings. A total of 100 adolescents were surveyed and 20 adolescents were interviewed to collect data for the study. The results show that adolescents share, rather than hide, their Facebook Content when they are connected with their mothers. The major themes on why they share Facebook Content are Infrequent Posting, Mother's Prior Knowledge, Confidence in Peers on Facebook, Transparency, and Permissive Parenting. On the other hand, the themes on why they hide Facebook Content from their mother are Differing Views from Mother, Unsolicited Attention, Conflict Avoidance, Filtered Posts Already, and their Preference to Withhold Facebook Content from All. In conclusion, the study yielded that mother-adolescent closeness is a large determining factor in the disclosing behavior of adolescents, and their desire to avoid conflict with their mothers is the foremost reason for withholding information on Facebook.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Internet and teenagers -- Philippines